Motivasi Orang Tua Mengikutsertakan Anaknya Dan Motivasi Anak Mengikuti Klub Renang Hasics Swimming Club Bojonegoro - Ardhana Hari Pangestu; Pudjijuniarto Pudjijuniarto (Intellektika : Jurnal Ilmiah Mahasiswa, 2024)
Swimming is a popular sport in the people of Bojonegoro. This encourages parents to encourage their children to study swimming. This research was conducted because of differences in parents' behavior towards children when practicing swimming at HasicsSwimming Club. There are parents who just include their children without knowingprogress of their child, and there are also those who are very supportive and even waitinghis son during practice from start to finish. So it has an impact onchildren's behavior when practicing. This research aims to find out whatparents' motivation to include their children and also knowing what the motivation isThe child joins the Hasics swimming clubSwimming Club. Research methodsused is descriptive quantitative with sampling (total sampling) namely 30 parents and children each. Each data was collected using a questionnaire, then the data was analyzed to be accumulated, then visualized using graphs. The results of this research are 1. parents' motivation to enroll their children in HasicsSwimming Club is from intrinsic factors, more precisely, namely becausedesire development and growth in children. 2. Motivate children to followHasics Swimming Club is because I want to be able to swim, socan improve swimming ability, for body fitness, forachieve your goals and want to deepen your knowledge about swimming.